Adaptation and Feasibility of the interRAI Family Carer Needs Assessment in a Pediatric Setting - Ioana A Stochitoiu; Christina Vadeboncoeur (SAGE Publishing, 2020)
Family carers of children with serious illness contribute many hours of medical care in addition to usual daily care. Assessing the needs and supports of family carers is not routine practice. This study is the first to utilize the interRAI Family Carer Needs Assessment in carers of children, seeking to evaluate and improve its ability to capture their needs. This is a prospective pilot study of family carers of children with serious illness receiving care at a pediatric hospice. Thirty carers completed the self-assessment form. Additional feedback was sought inquiring about the appropriateness of questions and missing information relevant to the pediatric setting. All participants reported the assessment captured important information across multiple domains. Additional questions surrounding extra costs, home and school supports, as well as direct impacts of caregiving activities on pain and relationships were identified as important adaptations. The most common unmet needs in carers and care recipients were episodic relief from caregiving (n=17) and housing adaptation (n=17), respectively. Overall, a comprehensive assessment form is feasible in identifying the diverse needs of family carers of children. Future research should focus on using pediatric specific interRAI tools to guide improvements in policy and practice that can address unmet needs.